2021
DOI: 10.1016/j.neo.2021.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk among MEN1, p53 and Notch regulates the proliferation of pancreatic neuroendocrine tumor cells by modulating INSM1 expression and subcellular localization

Abstract: Genomic analysis of Pancreatic Neuroendocrine Tumors (PanNETs) has revealed that these tumors often lack mutations in typical cancer-related genes such as the tumor suppressor gene p53 . Instead, PanNET tumorigenesis usually involves mutations in specific PanNET-related genes, such as tumor suppressor gene MEN1 . Using a PanNET mouse model, human tissues and human cell lines, we studied the cross-talk among MEN1, p53 and Notch signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The potential mechanisms of carcinogenesis associated with the oncogenic activity of Notch involve such biological events as the control of the phenotype of cancer-initiating cells, upregulation of tumour-associated signalling factors such as P53, facilitation of tumour angiogenesis and invasion, and cell cycle regulation [ 8 , 9 , 10 ]. It should also be noted that Notch may function as a tumour suppressor in other cancers, like squamous cell carcinoma (SCC) and neuroendocrine tumours [ 40 ]. The anti-tumour activity is related to the regulation of the malignant transcription factors, downstream suppressor gene activation and suppression of the cell cycle [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanisms of carcinogenesis associated with the oncogenic activity of Notch involve such biological events as the control of the phenotype of cancer-initiating cells, upregulation of tumour-associated signalling factors such as P53, facilitation of tumour angiogenesis and invasion, and cell cycle regulation [ 8 , 9 , 10 ]. It should also be noted that Notch may function as a tumour suppressor in other cancers, like squamous cell carcinoma (SCC) and neuroendocrine tumours [ 40 ]. The anti-tumour activity is related to the regulation of the malignant transcription factors, downstream suppressor gene activation and suppression of the cell cycle [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…High HNRNPC expression was correlated with recurrence and PD-L1 expression, which may allow the development of a combinatorial therapeutic regimen using HNRNPC inhibitor and PD-L1 monoclonal antibody. Recent studies have shown that genomic mutations in PanNENs can be relevant to classify patients beyond their tumor grade and identify novel prognostic markers and therapeutic targets that could be relevant in the future for adjuvant therapy [ 56 ]. It will be interesting to investigate whether such a clinical approach is feasible in PanNENs with high HNRNPC expression in prospective clinical trials.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…This was confirmed by our in vitro studies that showed no differences in the proliferation assay. Most previous studies on tumor biology of pNEN have focused on the role of menin in pNEN cell growth, [43][44][45] but its effect on metastasis of pNEN is mainly unknown. 46 This study demonstrated that the absence of menin activated the migration and invasion abilities modifications in different environments.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies on tumor biology of pNEN have focused on the role of menin in pNEN cell growth, 43 , 44 , 45 but its effect on metastasis of pNEN is mainly unknown. 46 This study demonstrated that the absence of menin activated the migration and invasion abilities of BON1 cells by increasing PTN expression.…”
Section: Discussionmentioning
confidence: 99%